Taxonomic study of Marinomonas strains isolated from the seagrass Posidonia oceanica, with descriptions of Marinomonas balearica sp nov and Marinomonas pollencensis sp nov. - Espinosa, Elena; Marco-Noales, Ester; Gomez, Daniel; Lucas-Elio, Patricia; Ordax, Mónica; Garcias-Bonet, Neus; Duarte, Carlos M.; Sanchez-Amat, Antonio (2017)
Novel aerobic, Gram-negative bacteria with DNA G + C contents below 50 mol% were isolated from the culturable microbiota associated with the Mediterranean seagrass Posidonia oceanica. 16S rRNA gene sequence analyses revealed that they belong to the genus Marinomonas. Strain IVIA-Po-186 is a strain of the species Marinomonas mediterranea, showing 99.77% 16S rRNA gene sequence similarity with the type strain, MMB-1(T), and sharing all phenotypic characteristics studied. This is the first description of this species forming part of the microbiota of a marine plant. A second strain, designated IVIA-Po-101(T), was closely related to M. mediterranea based on phylogenetic studies. However, it differed in characteristics such as melanin synthesis and tyrosinase, laccase and antimicrobial activities. In addition, strain IVIA-Po-101(T) was auxotrophic and unable to use acetate. IVIA-Po-101(T) shared 97.86% 16S rRNA gene sequence similarity with M. mediterranea MMB-1(T), but the level of DNA-DNA relatedness between the two strains was only 10.3%. On the basis of these data, strain IVIA-Po-101(T) is considered to represent a novel species of the genus Marinomonas, for which the name Marinomonas balearica sp. nov. is proposed. The type strain is IVIA-Po-101(T) (=CECT 7378(T) =NCIMB 14432(T)). A third novel strain, IVIA-Po-185(T), was phylogenetically distant from all recognized Marinomonas species. It shared the highest 16S rRNA gene sequence similarity (97.4%) with the type strain of Marinomonas pontica, but the level of DNA-DNA relatedness between the two strains was only 14.5%. A differential chemotaxonomic marker of this strain in the genus Marinomonas is the presence of the fatty acid C(17:0) cyclo. Strain IVIA-Po-185(T) is thus considered to represent a second novel species of the genus, for which the name Marinomonas pollencensis sp. nov. is proposed. The type strain is IVIA-Po-185(T) (=CECT 7375(T) =NCIMB 14435(T)). An emended description of the genus Marinomonas is given based on the description of these two novel species, as well as other Marinomonas species described after the original description of the genus.